Role of Festuca rubra and Festuca arundinacea in determinig the functional and genetic diversity of microorganisms and of the enzymatic activity in the soil polluted with diesel oil - Borowik, Agata (Environ Sci Pollut Res Int, 2019)
The objective of this study was to analyze the effect of two grass species, i.e. red fescue (Festuca rubra) and tall fescue (F. arundinacea), on the functional and genetic diversity of soil-dwelling microorganisms and on the enzymatic activity of soil not polluted and polluted with diesel oil. Grasses were examined for their effectiveness in accelerating degradation of PAHs introduced into soil with diesel oil. A growing experiment was conducted in Kick-Brauckman pots. The soil not polluted and polluted with diesel oil (7 cm(3) kg(-1) d.m.) was determined for the count of bacteria, colony development index, ecophysiological diversity index, functional diversity (using Biolog system), genetic diversity of bacteria (using NGS), enzymatic activity, and content of hydrocarbons. Study results demonstrated disturbed homeostasis of soil. The toxic effect of diesel oil on grasses alleviate with time since soil pollution. The yield of the first swath of red fescue decreased by 98% and that of tall fescue by 92%, whereas the yields of the second swath decreased by 82% and 89%, and these of the third swath by 50% and 47%, respectively. Diesel oil diminished also the functional and genetic diversity of bacteria. The use of grasses significantly decreased contents of C(6)-C(12) (gasoline total), C(12)-C(35) mineral oils, BTEX (volatile aromatic hydrocarbons), and PAHs in the soil, as well as enabled restoring the microbiological equilibrium in the soil, and increased functional and genetic diversity of bacteria. For this reason, both analyzed grass species, i.e. Festuca rubra and F. arundinacea, may be recommended for the remediation of soil polluted with diesel oil.